1995
DOI: 10.1007/bf00752317
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic and van Hove Scenarios for the cuprates: Taking the best of both worlds

Abstract: The purpose of this paper is to describe a microscopically-based theory of the cuprates that combines the strong features of the above described antiferromagnetic and van Hove scenarios. The first step in the construction of such a theory is the observation that the ARPES quasiparticle dispersion may be caused by holes moving in a local antiferromagnetic environment, rather than by band structure effects. This idea is motivated by the existence of universal flat bands [5][6][7] near k = (π, 0), (0, π) in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Not infrequently YBa 2 Cu 3 O 7 has been presented as the archetypal HTSC material and indeed through its planes and chains it would make direct show of formally Cu 2+ planar sites (with their attendant d 9 Jahn-Teller distortion) and formally Cu 3+ chain sites (with characteristic d 8 square-planar coordination). However, this crystallographic separation of formal valence in YBa 2 Cu 3 O 7 masks the role of the chains in introducing holes and metallicity to the planes and chains alike.…”
Section: Negative-u Modelling In the Two-subsystem Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Not infrequently YBa 2 Cu 3 O 7 has been presented as the archetypal HTSC material and indeed through its planes and chains it would make direct show of formally Cu 2+ planar sites (with their attendant d 9 Jahn-Teller distortion) and formally Cu 3+ chain sites (with characteristic d 8 square-planar coordination). However, this crystallographic separation of formal valence in YBa 2 Cu 3 O 7 masks the role of the chains in introducing holes and metallicity to the planes and chains alike.…”
Section: Negative-u Modelling In the Two-subsystem Environmentmentioning
confidence: 99%
“…HTSC phenomena do nonetheless clearly entail a considerable degree of coupling to the lattice, as witnessed by the wide variety of structural modifications registered around T c [36]. Such changes directly follow in the wake of specific electronic adjustments to site carrier counts (both static and dynamic), as, for example, the d 9 Jahn-Teller distortion. It is inevitable here, just as with CDWs, that in the prevailing highly-correlated circumstances charge and lattice are closely coupled.…”
Section: Negative-u Modelling In the Two-subsystem Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental and theoretical work of Gofron et al [23], Dagotto et al [24], and Beenen and Edwards [25] has demonstrated how within the framework of a generalized Hubbard model (but still excluding any double occupancy) spin-fluctuation phenomena may become expressly associated with a very considerable sharpening up of the LDA van Hove singularities. Such sharpening is what, it has been claimed, is manifest in the 'giant anomalous extension' of the vHs features detected in angle-resolved photoemission data above T c [26].…”
mentioning
confidence: 99%